Core-shell type vanadium-based metal oxide catalyst and preparation method and application thereof
By introducing a core-shell structure modified with alkaline earth metal surface into the catalyst, coupling the alkaline earth metal vanadate and metal oxide nanoparticle sites, the existing catalyst activity and selectivity are solved, and high conversion rate and high Selective propylene production reduces oxygen usage costs and improves safety.
Patent Information
- Application Number
- CN202310248967.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-15
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-03-15
AI Technical Summary
It is difficult for existing propane oxidation dehydrogenation catalysts to achieve high activity and high selectivity at the same time, resulting in the inability to achieve both propane conversion and propylene selectivity, and there are safety hazards and high economic costs.
The core-shell vanadium-based metal oxide catalyst is modified with alkaline earth metal surface. By coupling alkaline earth metal vanadate sites and metal oxide nanoparticle sites on the nanoscale, a catalyst with bifunctional sites is formed to realize the catalyst and reaction. The space and function of objects are decoupled.
Without sacrificing the propane conversion rate, the propylene selectivity is significantly improved, the oxygen usage cost is reduced, the deep oxidation products and safety risks are reduced, and the cycle stability of the catalyst is improved.
Smart Images

Figure CN116139870B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of low-carbon alkane chemical chain oxidative dehydrogenation catalysts, and specifically relates to a core-shell type composite metal oxide catalyst and a preparation method and application thereof. Background Art
[0002] Propylene is one of the most important chemical raw materials and the basic raw material for three major synthetic materials. Among the many emerging propylene production processes, the propane dehydrogenation process with high economic efficiency has attracted widespread attention. At present, the Oleflex process of UOP in the United States and the Catofin process of ABB & Lummus are widely used in industry. However, propane dehydrogenation is a strong endothermic reaction that needs to be operated at high temperature, and the conversion rate is limited by thermodynamic equilibrium. In order to improve the equilibrium conversion rate, high reaction temperature, low reaction pressure or dilution of feed gas strategies are usually adopted. However, the implementation of the above strategies often introduces additional operating costs, accelerates the occurrence of side reactions and deactivates catalysts. Propane oxidative dehydrogenation (ODH) is an exothermic reaction that is not limited by thermodynamic equilibrium and is considered to be another innovative way to produce propylene from propane. However, ODH is a challenging reaction because there are safety risks in the co-feeding of propane and oxygen, and the high economic cost of pure oxygen as a reactant, as well as the excessive oxidation of alkane molecules in an oxygen atmosphere, have become the main factors restricting its commercialization.
[0003] As an efficient and promising energy conversion technology, the chemical looping process is expected to achieve efficient and clean utilization of low-carbon alkanes. Its essence is to decouple a chemical reaction into two or more independent reactions. In the chemical looping propane oxidative dehydrogenation (CL-ODHP) process, metal oxides (also known as oxygen carriers) are used as media to recycle and replenish the lattice oxygen of the oxygen carrier between the reduction bed and the oxidation bed, which can effectively separate the oxygen removal and replenishment processes in the lattice in space or time. The key to the implementation of this technology lies in the design and development of efficient oxygen carriers, because oxygen carriers must simultaneously play multiple roles as catalysts (CH bond activation) and reactants (lattice oxygen supply). At present, the oxygen carriers used for CL-ODH are mainly single-component metal oxides (vanadium oxide, chromium oxide, tungsten oxide, etc.), but it is difficult to achieve high activity and high selectivity to activate propane to propylene at the same time. In recent years, researchers have started from regulating the lattice oxygen environment and used oxide-carrier interactions and transition metal doping to enhance the interaction of metal oxygen bonds to inhibit the excessive oxidation of lattice oxygen. However, this strategy often sacrifices activity in exchange for high propylene selectivity. Therefore, how to develop a chemical chain propane oxidative dehydrogenation catalyst with both high activity and high selectivity has become a key technical problem that needs to be solved urgently. Summary of the invention
[0004] The present invention aims to solve the technical problems related to the application of catalysts in the oxidative dehydrogenation of chemical chains of low-carbon alkanes, and provides a core-shell type vanadium-based metal oxide catalyst modified with an alkaline earth metal surface, a preparation method and an application. The core-shell catalyst can couple the alkaline earth metal vanadate site with the selective activation ability of CH bonds and the metal oxide site of bulk oxygen supply at the nanoscale, wherein the alkaline earth metal vanadate serves as the oxidative dehydrogenation catalytic site and the metal oxide nanoparticles serve as the bulk oxygen supply site. The core-shell catalyst obtained by the present invention decouples the oxygen carrier space and function that simultaneously serves as a catalyst (CH bond activation) and a reactant (lattice oxygen supply) at the nanoscale, effectively breaking the restrictive relationship that propane conversion rate and propylene selectivity cannot be obtained at the same time, and has the outstanding advantages of high conversion rate of low-carbon alkanes per pass and high selectivity of target product olefins.
[0005] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0006] According to one aspect of the present invention, a core-shell type vanadium-based metal oxide catalyst is provided, comprising a core and a surface shell, wherein the core is a metal oxide nanoparticle containing at least metal vanadium, and the surface shell is an alkaline earth metal vanadate generated by a solid phase reaction between vanadium oxide and alkaline earth metal oxide; the metal oxide nanoparticle serves as a bulk oxygen supplier, and the alkaline earth metal vanadate serves as a catalytic active site;
[0007] Wherein, the metal A other than metal vanadium in the metal oxide nanoparticles is at least one of Fe, Bi, and Mn;
[0008] Wherein, the alkaline earth metal B in the alkaline earth metal vanadate is at least one of Mg, Ca, Sr and Ba.
[0009] Preferably, the mass of the metal A is 0-40 wt.% of the total mass of the catalyst; the mass of the alkaline earth metal B is 1-20 wt.% of the total mass of the catalyst.
[0010] Preferably, the particle size of the metal oxide nanoparticles is 100-200 nm, and the thickness of the surface shell is 1-10 nm.
[0011] According to another aspect of the present invention, a method for preparing the core-shell type vanadium-based metal oxide catalyst is provided, and the method is carried out according to the following steps:
[0012] (1) dissolving a precursor salt of metal A and a precursor salt of vanadium in water respectively, and then mixing the two evenly; and then heating the mixed solution in a water bath and evaporating it to dryness; wherein metal A is at least one of Fe, Bi, and Mn;
[0013] (2) drying the substance obtained in step (1) and then calcining it in an air atmosphere at a temperature of 500-700° C. to obtain the metal oxide nanoparticles;
[0014] (3) dissolving a precursor salt of metal B in water to form an impregnation solution, and impregnating the impregnation solution onto the metal oxide nanoparticles obtained in step (2); wherein the metal B is at least one of Mg, Ca, Sr, and Ba;
[0015] (4) drying the material obtained in step (3) and then calcining it in an air atmosphere at a temperature of 500-700° C.; after calcining, the core-shell type vanadium-based metal oxide catalyst is obtained.
[0016] Preferably, the precursor salt of metal A in step (1) is at least one of ferric nitrate, bismuth nitrate and manganese nitrate, and the vanadium precursor salt is a mixture of ammonium metavanadate and a complexing agent.
[0017] Preferably, the precursor salt of metal B in step (3) is at least one of magnesium nitrate, calcium nitrate, strontium nitrate and barium nitrate.
[0018] Preferably, in step (2) and step (4), the drying temperature is 80-100° C., the drying time is 6-12 hours, and the roasting time is 1-8 hours.
[0019] According to another aspect of the present invention, there is provided an application of the core-shell type vanadium-based metal oxide catalyst for chemical chain oxidative dehydrogenation of low-carbon alkanes:
[0020] Under the condition of no oxygen co-feed, the catalyst reacts with low-carbon alkanes, and the alkaline earth metal vanadate serves as an oxidative dehydrogenation catalytic site to convert low-carbon alkanes into corresponding olefins and water; the metal oxide in the metal oxide nanoparticles serves as an oxygen supplier to replenish the lattice oxygen consumed on the surface, and the metal in the metal oxide is reduced to a low-valent state; oxygen or air is introduced into the catalyst after the reaction for regeneration, and the lattice oxygen in the low-valent metal oxide is replenished, while the carbon deposits are burned and heat energy is released; after the above cycle, the catalyst returns to its initial state.
[0021] Preferably, the carbon number of the low carbon alkane is 2-4.
[0022] Preferably, after the catalyst is pressed into tablets and sieved, it is physically mixed evenly with quartz sand in a mass ratio of (0.2-1):1; the reaction is carried out under normal pressure at a reaction temperature of 450-650°C; nitrogen is pre-introduced to exclude air, and then light alkanes are introduced; wherein the total flow rate of light alkanes and nitrogen is 20-50 ml / min, and the volume percentage of light alkanes is 5-30%.
[0023] The beneficial effects of the present invention are:
[0024] The alkaline earth metal surface modified vanadium-based metal oxide catalyst of the present invention has a core-shell structure with dual functional sites at the nanoscale, which is specifically manifested in coupling the alkaline earth metal vanadate site with CH bond selective activation ability and the metal oxide site of bulk oxygen supply, wherein the alkaline earth metal vanadate is used as the oxidative dehydrogenation catalytic site and the metal oxide nanoparticle is used as the bulk oxygen supply site; it decouples the oxygen carrier space and function of both the catalyst (CH bond activation) and the reactant (lattice oxygen supply) at the nanoscale, and has high propylene selectivity without sacrificing the propane conversion rate, effectively breaking the restrictive relationship that the propane conversion rate and propylene selectivity cannot be obtained at the same time; and it has the outstanding advantages of high conversion rate of low-carbon alkanes per pass and high selectivity of target product olefins. At the same time, the introduction of vanadium elements in the bulk metal oxide nanoparticles to construct transition metal / rare earth metal vanadates can effectively solve the problems of sintering of pure iron oxide, bismuth oxide, etc. during the redox process, loss and deactivation of metal bismuth, and low oxygen loading.
[0025] The preparation method of the core-shell type vanadium-based metal oxide modified with alkaline earth metal surface adopts a two-step preparation method of coprecipitation-impregnation method, which has low cost, simple operation and easy scale-up production; at the same time, cheap and easily available oxides and alkaline earth metals (calcium, magnesium and barium) with abundant reserves are adopted.
[0026] The alkaline earth metal surface modified vanadium-based metal oxide catalyst of the present invention has a core-shell structure with dual functional sites on the nanometer scale, which is characterized by alkaline earth metal vanadate sites with oxidative dehydrogenation catalytic activity and selectivity loaded on the surface of metal oxide nanoparticles; the generation of this structure depends on the in-situ generation of the shell layer of alkaline earth metal vanadate after the alkaline earth metal is loaded on the surface of the metal oxide nanoparticles, dried and calcined. By adjusting the alkaline earth metal loading, surface shells of different thicknesses and compositions can be obtained, and then a core-shell catalyst with an optimal propylene yield can be obtained. Compared with single metal oxide nanoparticles, the selectivity of low-carbon olefins is significantly improved; compared with single alkaline earth metal vanadate, the conversion rate of low-carbon alkanes is improved. The catalyst after the reaction is regenerated by introducing oxygen or air, the lattice oxygen of the low-valent catalyst is supplemented, and the carbon deposits are effectively burned at the same time, and the generated heat is transferred through the catalyst medium. By adjusting the mass of the catalyst, a high degree of heat matching can be achieved. Compared with the existing technology, the direct use of oxygen is avoided, the high cost of air separation is saved, the formation of deep oxidation products is reduced, and the safety hazard of mixing reducing and oxidizing gases is eliminated. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1The graphs are propane conversion, product selectivity and propylene yield of the catalysts prepared in Examples 1-8 of the present invention in the chemical chain propane oxidative dehydrogenation reaction;
[0028] Figure 2 The X-ray diffraction (XRD) and Raman test result spectra of the catalysts prepared in Examples 1-8 of the present invention;
[0029] Figure 3 Figure (a) shows the propane conversion rate, product selectivity and propylene yield in the chemical chain propane oxidative dehydrogenation reaction of the catalysts prepared in Examples 1, 8, 12 and 13 of the present invention, and the ammonia temperature programmed desorption (NH3-TPD) graph (b);
[0030] Figure 4 The X-ray diffraction (XRD) and Raman test result spectra of the catalysts prepared in Examples 1, 8, 12, and 13 of the present invention are shown;
[0031] Figure 5 The high angle annular dark field scanning transmission electron microscope (HAADF-STEM) images and energy spectrum analysis surface scanning (EDS-MAPPING) images of the catalysts prepared in Examples 1, 12, and 13 of the present invention respectively show the distribution diagrams of O element, Fe element, V element, and Mg element: (a) 5Mg / FeVO4, (b) 10Mg / FeVO4, (c) 20Mg / FeVO4;
[0032] Figure 6 The hydrogen temperature-programmed reduction (H2-TPR) and oxygen temperature-programmed desorption (O2-TPD) diagrams of the catalysts prepared in Examples 1, 8, 12, and 13 of the present invention are shown;
[0033] Figure 7 Thermogravimetric test diagrams of the catalysts prepared in Examples 1, 8, 12, and 13 of the present invention: (a) mass change diagram, (b) oxygen storage diagram;
[0034] Figure 8 These are the test results of the cyclic stability of the 10Mg / FeVO4 core-shell catalyst prepared in Example 12 of the present invention. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below through specific examples. The following examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way.
[0036] Embodiment 1:
[0037] Step 1, taking 5.0 parts by mass of ferric nitrate and uniformly dissolving it in 200.0 mL of deionized water to form solution-1;
[0038] 1.5 parts by mass of ammonium metavanadate and 2.5 parts by mass of citric acid were uniformly mixed and dissolved in 200.0 mL of deionized water to form solution-2; in addition to citric acid, oxalic acid and the like may also be used as the complexing agent.
[0039] Add solution-2 into solution-1, stir, and place in a 100°C water bath for 3-4 hours. Evaporate the solution to dryness, and then dry at 80-100°C for 6-12 hours.
[0040] Then it is calcined in a muffle furnace, the calcination atmosphere is air, the calcination temperature is 550°C, and the calcination time is 1-8 hours; the molecular formula of the obtained catalyst is recorded as FeVO4.
[0041] Step 2: Take 0.55 parts by mass of magnesium nitrate and uniformly dissolve it in 1.0 mL of deionized water to form an impregnation solution.
[0042] Step 3: impregnate an equal volume of the impregnation solution obtained in step 2 onto the surface of 1.0 mass part of the FeVO4 catalyst obtained in step 1, and then dry at 80-100° C. for 6-12 hours.
[0043] Step 4, calcining the material obtained in step 3 in a muffle furnace, the calcination atmosphere is air, the calcination temperature is 550°C, and the calcination time is 1-8 hours; that is, a magnesium vanadate catalyst supported on FeVO4 is obtained, and the mass percentage of metallic magnesium is 5% based on the total mass of the core-shell catalyst, and its molecular formula is recorded as 5Mg / FeVO4.
[0044] Embodiment 2:
[0045] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 0.31 parts by mass of calcium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metallic calcium was 5%, and its molecular formula was recorded as 5Ca / FeVO4.
[0046] Embodiment 3:
[0047] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 0.13 parts by mass of strontium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metal strontium was 5%, and its molecular formula was recorded as 5Sr / FeVO4.
[0048] Embodiment 4:
[0049] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 0.10 parts by mass of barium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metal barium was 5%, and its molecular formula was recorded as 5Ba / FeVO4.
[0050] Embodiment 5:
[0051] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 0.52 parts by mass of lithium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metallic lithium was 5%, and its molecular formula was recorded as 5Li / FeVO4.
[0052] Embodiment 6:
[0053] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 0.19 parts by mass of sodium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metallic sodium was 5%, and its molecular formula was recorded as 5Na / FeVO4.
[0054] Embodiment 7:
[0055] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 0.13 parts by mass of potassium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metallic potassium was 5%, and its molecular formula was recorded as 5K / FeVO4.
[0056] Embodiment 8:
[0057] The preparation was carried out using the method of Example 1, the only difference being that only steps 1 and 5 were performed, and the molecular formula of the obtained catalyst was recorded as FeVO4.
[0058] Embodiment 9:
[0059] The preparation was carried out by the method of Example 1, the only difference being that the calcination temperature in steps 1 and 4 was 600°C.
[0060] Embodiment 10:
[0061] The preparation was carried out by the method of Example 1, the only difference being that the calcination temperature in steps 1 and 4 was 700°C.
[0062] Embodiment 11:
[0063] The preparation was carried out by the method of Example 1, the only difference being that the calcination temperature in steps 1 and 4 was 500°C.
[0064] Embodiment 12:
[0065] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 1.17 parts by mass of magnesium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metallic magnesium was 10%, and its molecular formula was recorded as 10Mg / FeVO4.
[0066] Embodiment 13:
[0067] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 2.63 parts by mass of magnesium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metallic magnesium was 20%, and its molecular formula was recorded as 20Mg / FeVO4.
[0068] Embodiment 14:
[0069] The preparation was carried out by the method of Example 1, the only difference being that in step 2, 0.11 parts by mass of magnesium nitrate was uniformly dissolved in 1.0 mL of deionized water to form an impregnation solution. Based on the total mass of the core-shell catalyst, the mass percentage of metallic magnesium was 1%, and its molecular formula was recorded as 1Mg / FeVO4.
[0070] Embodiment 15:
[0071] The preparation method of Example 1 is used, and the only difference is that in step 1, only 1.5 parts by mass of ammonium metavanadate and 2.5 parts by mass of citric acid are mixed evenly and dissolved in 200.0 mL of deionized water; in addition to citric acid, oxalic acid and the like can also be used as the complexing agent. Based on the total mass of the core-shell catalyst, the mass percentage of metal magnesium is 10%, and its molecular formula is recorded as 10Mg / V2O5
[0072] Embodiment 16:
[0073] The preparation was carried out by the method of Example 1, the only difference being that in step 1, 6.2 parts by mass of bismuth nitrate and 2.5 parts by mass of citric acid were mixed evenly and dissolved in 200.0 mL of deionized water to form solution-1. Based on the total mass of the core-shell catalyst, the mass percentage of metallic magnesium was 5%, and its molecular formula was recorded as 5Mg / BiVO4.
[0074] Embodiment 17:
[0075] The preparation was carried out by the method of Example 1, except that in step 1, 4.6 parts by mass of an aqueous solution of manganese nitrate and 2.5 parts by mass of citric acid were mixed evenly and dissolved in 200.0 mL of deionized water to form solution-1. Based on the total mass of the core-shell catalyst, the mass percentage of metallic magnesium was 5%, and its molecular formula was recorded as 5Mg / Mn2V2O7.
[0076] The core-shell catalysts obtained in Examples 1-7 and 9-17 and the FeVO4 obtained in Example 8 were naturally cooled to room temperature, pressed into tablets, and sieved to form granular catalysts with a size of 20-40 mesh. Then 0.2-0.8 g was weighed and mixed with quartz sand (SiC). The experiment was carried out in a fixed bed tubular reactor at a reaction temperature of 450-600°C and a pressure of 1 atmosphere. Before the reaction, N2 was introduced to exhaust oxygen and air in the tubular reactor, and then propane was introduced, wherein the total flow rate of propane and nitrogen was 20 mL / min, and the volume fraction of propane was 10%. The product composition was detected by gas chromatography.
[0077] The propane conversion rate is calculated by the following formula:
[0078]
[0079] actually:
[0080] ——Propane conversion rate, %
[0081] ——Molar flow rate of propane at reactor inlet, moL / min
[0082] ——Molar flow rate of propane at reactor outlet, moL / min
[0083] The product gas phase selectivity is calculated by the following formula:
[0084]
[0085] in:
[0086] S 产物A ——Selectivity of gas phase product A, %
[0087] n 产物A ——Production of gas phase product A, moL
[0088] ∑ n产物 ——The sum of the amounts of all product substances in the gas phase, moL
[0089] x 产物A ——The content of gas phase product A in all gas phase products
[0090] Gas phase products A include: C3H6, CO x (Carbon oxides, i.e. CO, CO2), CH4, C2H6, C2H4.
[0091] The performance of the catalysts obtained in Examples 1-8 was evaluated. Figure 1As shown, the solid dot graph represents propane conversion, the bar graph shows product selectivity, and the dotted triangle graph represents propylene yield. FeVO4 without surface modification is more inclined to over-oxidize propane. The propane conversion rate of FeVO4 catalysts modified with alkali metals (Li, Na, K) is almost zero, which greatly passivates the activation ability of CH bonds. Among the four alkaline earth metals of Mg, Ca, Sr, and Ba, the magnesium-modified FeVO4 catalyst can improve the selectivity of propylene to a certain extent without sacrificing the propane conversion rate, and has the highest propylene yield.
[0092] The catalysts obtained in Examples 1-8 were further characterized by XRD and Raman structures. Figure 2 As shown in the figure, the XRD characteristic peaks of FeVO4 catalysts modified by alkali metals (Li, Na, K) and alkaline earth metals (Mg) changed, proving that the surface structure underwent a phase change. The formation of alkali metal vanadates is the main reason for the loss of its CH bond activation ability. The magnesium-modified FeVO4 catalyst also underwent a phase change, and while retaining the iron vanadate structure, a new Mg2V2O7 structure was generated, which may be the reason for its improved selectivity. Raman structural characterization was further confirmed.
[0093] The performance of the catalysts of Examples 1, 8, 12, and 13 was further evaluated. Figure 3 As shown, the solid dot graph represents propane conversion, the bar graph shows product selectivity, and the dotted triangle graph represents propylene yield. The propylene selectivity shows a trend of first increasing and then decreasing with the increase of the content of surface-modified magnesium, and the propylene yield also shows a volcanic peak relationship. It is worth noting that the propane conversion rate was not suppressed. The results of the programmed temperature desorption experiment (NH3-TPD) using ammonia as a probe molecule showed that the surface acidity changed significantly with the increase of the content of surface-modified magnesium, which indicates that the modification of magnesium causes structural changes on the surface of iron vanadate, which may be the reason for its improved selectivity.
[0094] In order to further explore the structural changes on the surface of iron vanadate caused by magnesium modification, XRD and Raman structural characterization were performed on the catalysts of Examples 1, 8, 12, and 13. Figure 4 The results show that as the magnesium modification amount increases from 5% to 10% and then to 20%, the shell structure changes from Mg2V2O7 to Mg3V2O7. This conclusion is further confirmed by STEM-EDS mapping results ( Figure 5). The introduction of magnesium of appropriate mass can form a dense Mg2V2O7 structure on the surface of FeVO4, which is conducive to the selective oxidation of propane and thus improves the selectivity of propylene. The introduction of excessive magnesium will lead to the formation of Mg3V2O7 structure in the shell, which tends to over-oxidize propane and reduce the selectivity of propylene. At the same time, the core of the core-shell catalyst can also be extended to vanadium-based composite metal oxides such as vanadium oxide, vanadium bismuth, and vanadium manganese. The vanadium-based metal oxide catalyst modified by alkaline earth metal surface has a core-shell structure with dual functional sites at the nanoscale, which is manifested as alkaline earth metal vanadate (B=Mg, Ca, Sr, Ba) sites with oxidative dehydrogenation catalytic activity and selectivity loaded on the surface of metal oxide (A=Fe, Bi, Mn) nanoparticles. The formation of this structure depends on the in-situ generation of the shell of alkaline earth metal vanadate after the alkaline earth metal is loaded on the surface of the metal oxide (A=Fe, Bi, Mn) nanoparticles, dried, and calcined. By adjusting the calcination temperature and the alkaline earth metal loading, a core-shell catalyst with a metal oxide nanoparticle with a particle size of 100-200nm and a surface shell layer with a thickness of 1-10nm can be obtained, and then a core-shell catalyst with an optimal propylene yield can be obtained. The oxygen carrier space and function that simultaneously serves as a catalyst (CH bond activation) and a reactant (lattice oxygen supply) are decoupled at the nanoscale, and high propylene selectivity is achieved without sacrificing propane conversion, effectively breaking the restrictive relationship that propane conversion and propylene selectivity cannot be achieved at the same time. According to the comparison of the embodiments, the calcination temperature of the core-shell catalyst of 500-700°C and the mass of metal B accounting for 5-10wt.% of the total mass of the catalyst have better effects.
[0095] The core-shell catalyst prepared in the present invention was further subjected to H2-TPR test, and the results were as follows: Figure 6 As shown in the figure, with the increase of Mg modification content, the reduction peak first shifts to the high temperature direction and then to the low temperature direction, indicating that the metal oxygen bond of the dense Mg2V2O7 structure generated by the introduction of an appropriate amount of magnesium is relatively stronger. The lattice oxygen of the surface Mg3V2O7 structure generated by the introduction of excessive magnesium is more active. This conclusion is further confirmed by the O2-TPD results.
[0096] The core-shell catalyst prepared in the present invention was further subjected to thermogravimetric (TG) testing, and the results are as follows: Figure 7 As shown, with the increase of Mg modification content, the oxygen release rate gradually increases, indicating that an active shell is constructed on the surface, which can also pull the release of bulk lattice oxygen, thereby achieving high propylene selectivity without sacrificing propane conversion rate, effectively breaking the restrictive relationship that propane conversion rate and propylene selectivity cannot be achieved at the same time.
[0097] The 10Mg / FeVO4 core-shell catalyst prepared in the present invention was further subjected to a cyclic stability test. The results are as follows: Figure 8As shown, the solid dot graph represents propane conversion, the solid square graph shows propylene selectivity, and the dotted triangle graph represents propylene yield. The catalyst performance remained basically unchanged during the chemical chain propane oxidative dehydrogenation cycle stability test, indicating that the core-shell composite metal oxide has good oxidative regeneration performance.
[0098] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the present invention and the claims, all of which fall within the scope of protection of the present invention.
Claims
1. An application of a core-shell vanadium-based metal oxide catalyst, characterized in that: Used for chemical chain oxidative dehydrogenation of low carbon alkanes; The core-shell type vanadium-based metal oxide catalyst comprises a core and a surface shell, wherein the core is a metal oxide nanoparticle containing at least metal vanadium, and the surface shell is an alkaline earth metal vanadate generated by a solid phase reaction between vanadium oxide and alkaline earth metal oxide; the metal oxide nanoparticle serves as a bulk oxygen supplier, and the alkaline earth metal vanadate serves as a catalytic active site; Wherein, the metal A other than metal vanadium in the metal oxide nanoparticles is Fe; Wherein, the alkaline earth metal B in the alkaline earth metal vanadate is at least one of Mg, Ca, Sr and Ba; The core-shell type vanadium-based metal oxide catalyst is prepared according to the following steps: (1) Dissolving a precursor salt of metal A and a precursor salt of vanadium in water respectively, and then mixing the two evenly; and then heating the mixed solution in a water bath and evaporating to dryness; wherein metal A is Fe; (2) drying the substance obtained in step (1) and then calcining it in an air atmosphere at a temperature of 500-700° C. to obtain the metal oxide nanoparticles; (3) dissolving a precursor salt of metal B in water to form an impregnation solution, and impregnating the impregnation solution onto the metal oxide nanoparticles obtained in step (2); wherein metal B is at least one of Mg, Ca, Sr, and Ba; (4) drying the substance obtained in step (3) and then calcining it in an air atmosphere at a temperature of 500-700° C.; after calcination, the core-shell type vanadium-based composite metal oxide catalyst is obtained; Under the condition of no oxygen co-feed, the core-shell type vanadium-based metal oxide catalyst reacts with low-carbon alkanes, the reaction is carried out at normal pressure, and the reaction temperature is 450-650°C; the alkaline earth metal vanadate serves as an oxidative dehydrogenation catalytic site to convert low-carbon alkanes into corresponding olefins and water; the metal oxide in the metal oxide nanoparticles serves as an oxygen supplier to replenish the lattice oxygen consumed on the surface, and the metal in the metal oxide is reduced to a low-valent state; oxygen or air is introduced into the core-shell type vanadium-based metal oxide catalyst after the reaction for regeneration, the lattice oxygen in the low-valent metal oxide is replenished, and the carbon deposits are burned and heat energy is released; after the above cycle, the core-shell type vanadium-based metal oxide catalyst returns to its initial state.
2. The use of a core-shell type vanadium-based metal oxide catalyst according to claim 1, characterized in that: The mass of the metal A is 0-30 wt.% of the total mass of the catalyst; the mass of the alkaline earth metal B is 1-20 wt.% of the total mass of the catalyst.
3. The use of a core-shell type vanadium-based metal oxide catalyst according to claim 1, characterized in that: The particle size of the metal oxide nanoparticles is 100-200 nm, and the thickness of the surface shell is 1-10 nm.
4. The use of a core-shell type vanadium-based metal oxide catalyst according to claim 1, characterized in that: The carbon number of the low carbon alkane is 2-4.
5. The use of a core-shell type vanadium-based metal oxide catalyst according to claim 1, characterized in that: The core-shell type vanadium-based metal oxide catalyst is pressed into tablets and sieved, and then physically mixed with quartz sand in a mass ratio of (0.2-1):1; nitrogen is pre-introduced to exclude air, and then low-carbon alkanes are introduced; wherein the total flow rate of low-carbon alkanes and nitrogen is 20-50 mL / min, and the volume percentage of low-carbon alkanes is 5-30%.
6. The use of the core-shell type vanadium-based metal oxide catalyst according to claim 1, characterized in that: The precursor salt of metal A in step (1) is ferric nitrate, and the precursor salt of vanadium is a mixture of ammonium metavanadate and a complexing agent.
7. The use of the core-shell type vanadium-based metal oxide catalyst according to claim 1, characterized in that: The precursor salt of the metal B in step (3) is at least one of magnesium nitrate, calcium nitrate, strontium nitrate and barium nitrate.
8. The use of the core-shell type vanadium-based metal oxide catalyst according to claim 1, characterized in that: In step (2) and step (4), the drying temperature is 80-100° C., the drying time is 6-12 hours, and the roasting time is 1-8 hours.